SYNTHESIS AND ANALYTICAL STUDY OF A SPATIAL MECHANISM WITH TWO LEVELS OF MOBILITY OF A TURNING MACHINE - ZALYUBOVSKYI, MARK; PANASYUK, IGOR; KOSHEL, OLEXANDR; KOSHEL, OLEXANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Geometric synthesis of a statically determined spatial eight-link hinged mechanism with rotary kinematic pairs of a barreling machine, in which the working capacity carries out a complex spatial movement, followed by an analytical study of the structural features of the machine mechanism. An analytical approach was used in the study of the eight-link hinged mechanism with rotary kinematic pairs, which consists of geometric and structural synthesis, and the design of barreling machine was modeled in the SolidWorks 2021 automated design software. One of the possible options for freeing the spatial mechanism of the barreling machine from passive connection is proposed, the synthesis of a statically determined spatial eight-link hinged mechanism with rotational kinematics is carried out. An appropriate design of a barreling machine with two driving links has been developed, the use of which creates conditions for increasing its reliability during operation and simultaneously increasing the productivity of performing the corresponding barreling operations. Analytical studies of the main geometric and structural parameters of the barreling machine were carried out. The connection between the corresponding geometric parameters of the synthesized statically determined spatial eight-link mechanism is established, which allows determining the rational ratio of the lengths of its links to each other. The relationship between the lengths of the links, their position and the angle of swing of the rocker arm together with the drive shaft of the machine is established. The synthesis of a statically determined spatial eight-link hinged mechanism with rotary kinematic pairs with two degrees of mobility was performed. Based on the synthesis of the mechanism, a new design of the barreling machine with two driving links was developed. Mathematical expressions for calculating the main geometric relationships of the link lengths of the developed machine structure were obtained analytically.
Keywords: passive connection; statically determined mechanism; rotational kinematic pair; barreling